Radiographic evaluation of secondary alveolar graff in the closure of alveolar fissures of patients with cleft lip and palate - Acosta Rangel Monica C; Ozuna Ugalde Roberto (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
The X-ray evaluation of alveolar bone graft in lip-toveal palatines is one of the relevant topics in the management of this type of pathology since there are several studies conducted with parameters that are taken to determine the timing of the graft and its feasibility, as well as find the most accurate form and measure the integration of grafting dares of radiographic studies.  Objective: to measure the radiographic integration of secondary alveolar graft in the closure of alveolar fissures of patients with cleft lip and palate.  Material and method: observational, analytical, retrospective, longitudinal, descriptive, open, and series of cases from May 2013 to August 2019.  Results: The radiographic size of the preoperative and postoperative bone defect was measured, both on the Chelsea scale and the planimetry proposed in this study. In alveolar planimetry, Wilcoxon's test for horizontal dimension showed no significant difference, the vertical dimension in initial X-ray versus subsequent showed significant difference to treatment. For the Chelsea scale, a square Xi analysis was performed comparing initial vs. later X-rays, showing that there is significant difference.  Conclusions: The results demonstrate greater integration than reported in international literature. Orthopedic treatment, reaching GOSLON 1, helps us from a more stable and close anatomical state to reconstruction. The planimetry proposed in this study adds detail to other scales, as it showed more sensitivity than the Chelsea scale.